Risk Identification Of Public Private Partnership (PPP) Project In Railway Sector Makassar–Parepare Indonesia - Yusfira Afrianti Haq; Farida Rachmawati (IPTEK The Journal for Technology and Science, 2026)
Infrastructure development plays a crucial role in ensuring the sustainable economic growth of a country. For instance, Indonesia saw a 29.532% rise in infrastructure investments between 2015 and 2019, showcasing their heavy investment in infrastructure project. The Public Private Partnership (PPP) project in Indonesia is a collaborative effort between the government and private entities to enhance infrastructure project development. The Makassar-Parepare Railway Public Private Partnership (PPP) project is an example of a national strategic project on transportation sector, especially train transportation, which aims to improve the quality of national infrastructure and connectivity. However, the project faces various risks such as delays in determining the railway route and a lack of understanding of the Government Contracting Agency (GCA/PJPK) regarding the PPP concept. In order to ensure the success of this project, it is important to identify and manage these risks effectively. Utilizing the likert scale, a literature review uncovered 29 relevant risk factors, while the probability impact matrix (PIM) analysis aided in ranking the 18 main risks in the Makassar-Parepare Railway PPP project. This research can contribute to the development of more effective risk management strategies for similar infrastructure projects in the future.